2022
DOI: 10.3390/plants11233254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wood-Derived Biochar on Germination, Physiology, and Growth of European Beech (Fagus sylvatica L.) and Turkey Oak (Quercus cerris L.)

Abstract: Biochar (BC) soil amendments could partially counteract soil carbon (C) stock decrease in broad-leaved forests in Italy; however, its effects on the growth of representative tree species—Fagus sylvatica L. and Quercus cerris L.—has not yet been addressed. We examine whether seed germination and growth of these species are affected by addition of BC obtained from deciduous broadleaf trees. Seeds were left to germinate in greenhouse conditions under three different BC amendments: 0% (control), 10% and 20% (v/v).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
(73 reference statements)
1
1
0
Order By: Relevance
“…Specifically, it significantly affected both RL and GI, but not GN. Not significant changes in GN suggest that biochar did not affect seed endosperm weakening and the emergence of radicles (germination in the strict sense); this is consistent with previous works on maize [ 27 , 28 ], European beech, Turkey oak [ 29 ] and different herbaceous perennial species [ 30 ]. Nevertheless, biochar alone (100% treatments) clearly compromised GN.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, it significantly affected both RL and GI, but not GN. Not significant changes in GN suggest that biochar did not affect seed endosperm weakening and the emergence of radicles (germination in the strict sense); this is consistent with previous works on maize [ 27 , 28 ], European beech, Turkey oak [ 29 ] and different herbaceous perennial species [ 30 ]. Nevertheless, biochar alone (100% treatments) clearly compromised GN.…”
Section: Discussionsupporting
confidence: 91%
“…A large number of studies have shown that a combination of biochar and nitrogen, phosphorus, and potassium fertilisers can improve the growth and quality of forest trees, which is important for improving plant yield [21,22]. XiaoLi B et al [23] found that the addition of 1-2% biochar had a significant positive effect on the seed germination, aboveground, and root growth of Robinia pseudoacacia L. Li H et al [24] found that the combination of biochar and chemical fertilisers significantly improved the quality and yield of apples.…”
Section: Discussionmentioning
confidence: 99%